Obstructive sleep apnea and headache: an integrative review of the last 18 years - Fortes, Henry Martins Soares; Severiano, Rodrigo Simões Duarte; Barros, Pedro Pinheiro; Silva, Beatrice Martins da Costa; Freitas, Letícia Lima; Sena, Arthur dos Santos; Roberto, Robertina Pinheiro (Headache Medicine, 2022)
Introduction Obstructive sleep apnea (OSA) is a prevalent and underdiagnosed clinical condition, characterized by the presence of repetitive airway collapse during sleep, resulting in oxyhemoglobin desaturation and sleep fragmentation. Among the most frequent reports of patients with OSA, is morning headache or chronic daily headache, which in 2004 received its own classification in the International Classification of Headache Disorders (ICHD-2) as sleep apnea headache. Objective The present review aims to evaluate the available scientific literature on the association between OSA and headache after classification, totaling a period of 18 years. Results In 8 included studies, 1,637 patients were analyzed, observing a bilateral and frequent association between the two pathologies. Conclusion However, there is still no consensus on the mechanism behind this relationship, and the results of studies are divergent.